The best American poetry 2024 - Salter, Mary Jo; Salter, Mary Jo; Lehman, David, 1948-; Lehman, David, 1948- (Scribner Poetry, 2024)
"The Best American Poetry series has been "one of the mainstays of the poetry publication world" (Academy of American Poets) since 1988. Each volume presents a curated selection of the year's most brilliant, striking, and innovative poems, with comments from the poets themselves offering unique insight into their work. Here, guest editor Mary Jo Salter, whose own poems display a sublime wit "driven by a compulsion to confront the inexplicable" (James Longenbach), has picked seventy-five poems that capture the dynamism of American poetry today. The series and guest editors contribute valuable introductory essays that assess the current state of American poetry, and this year's edition is certain to capture the attention of both Best American Poetry loyalists and newcomers to the most important poetry anthology of our time." -- page 4 of cover.